Structure and physical properties evolution of ITO film during amorphous-crystalline transition using a highly effective annealing technique. Issue 13 (September 2019) - Li, Jiaming; Jiang, Liangbao; Chen, Mu; Li, Xiaoyu; Wei, Youxiu; Ma, Yibo; Fu, Ziyi; Yan, Yue
Abstract: Three kinds of amorphous ITO (a-ITO) films were deposited on chemically strengthened glass by DC magnetron sputtering at room temperature. A rapid infrared annealing (RIA) device was built, and an infrared fast crystallization process was developed. Not only the effects of RIA on the structural, optical, and electrical properties of ITO films, but also the effects of RIA on the mechanical properties of chemically strengthened glass substrates were investigated compared with those of conventional furnace annealing (CFA). The rules of the structural and physical properties during amorphous-crystalline transition are basically the same by RIA and CFA. However, the RIA time is only 10% of the CFA time, and the compressive stress reduction of chemically strengthened glass is only 4.2% at 500 °C, which is 38.5% by CFA. These results demonstrate that very effective RIA technology could replace the traditional annealing method (CFA), which can greatly reduce production costs and significantly improve production efficiency.